ขอบเขตรายจุดของฟังก์ชันโฮโลมอร์ฟิกซึ่งกำลังสองอินทิเกรดได้เทียบกับฟังก์ชันความหนาแน่นเอกซ์โพเนนเชียล - กำธร ไชยลึก (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
Let phi be a real-valued function on C satisfying 0< = delta phi < = M for some M>0. Denote by Hl2 (C,e - phi) the space of all holomorphic functions on C which are square-integrable with respect to the measure e -phi(z)dz. In this work, we obtain a pointwise bound of any function in this space. We can show that there exists a constant K depending only on phi such that [f(z)]2 <=Ke phi(z) [[f]]2 L2(C,e-phi) for any f in HL2(C,e-phi) and any z phi E C.